Design games for architecture : creating digital design tools with Unity - Westre, Aaron (New York : Routledge, Taylor & Francis Group, 2014)
Design Games teaches you how to create playful software tools based on your architectural design processes, whether or not you are familiar with game design technology. By working through exercises illustrated with screen shots and code, you acquire knowledge about each step required to build useful tools you can use to accomplish design tasks.
Introduction -- 1. Tools of the trade: Trying it out -- 2. Building blocks -- 3. Slingshot -- 4. Kirigami -- 5. Component -- 6. Showroom -- Conclusion.
Includes bibliographical references (pages 180-181) and index.
Keywords: Unity (Electronic resource).; Architecture -- Study and teaching; Architecture -- Problems, exercises, etc; Computer games -- Programming